Kearifan Lokal dari Olele: Tonggak Pemertahanan Budaya Maritim Gorontalo Pasca Pandemi Covid-19 - Salam, Aziz; Syamsuddin, Syamsuddin (The NIKe Journal, 2022)
This research aims to see to what extent the potential of local wisdom can become a bulwark for community self-defense from disasters such as pandemics. The Covid-19 outbreak has eroded various aspects of human life. The local wisdom of the Olele Village fishing community can be considered as a representation of the maritime culture of the Gorontalo ethnic community in general. The joints of socio-economic-cultural life in Olele Village, which are tightly bound by the local wisdom of its fishing community, have been able to convincingly survive the shock of the Covid-19 Pandemic. The local wisdom of the Oele Village fishing community has the potential to be maintained and developed into Gorontalo Maritime Culture so that it can become a milestone in the socio-economic and cultural maintenance of coastal communities in facing any difficult situations after the Covid-19 Pandemic in the future.